Changing roles of the corresponding author - Consequences for the accessibility of medical information - Olaf R. van Loon; A.J. (Tom) (Elsevier, 2023)
It appears that ever more frequently the corresponding author of a multi-author manuscript is not what he/she was originally supposed to be: the most involved researcher with the best overview concerning the presented study. Numerous journals now use the term 'corresponding author', however, for the author who acts as a kind of secretary for the submitted manuscript, irrespective of his/her expertize in the subject. Another problem is that a significant number of universities give more scientific credits to the corresponding author than to his/her co-authors, which fairly commonly results in granting the corresponding authorship to the student or young scientist who needs scientific credits most urgently for his/her academic career. Consequently, readers of a multi-author article are nowadays hardly able to judge which author of an interesting article might best be contacted for additional information. An increasing number of journals seem unaware of the problems that this changing role of the corresponding author may cause. The present contribution both mentions the main resulting problems and proposes possible solutions.